Non-standard Spatial Statistics and Spatial Econometrics - Griffith, Daniel A.; Paelinck, Jean H. Paul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Despite spatial statistics and spatial econometrics both being recent sprouts of the general tree "spatial analysis with measurement"$1 (Bsome may remember the debate after WWII about "theory without measurement" versus "measurement without theory"$1 (Bseveral general themes have emerged in the pertaining literature. But exploring selected other fields of possible interest is tantalizing, and this is what the authors intend to report here, hoping that they will suscitate interest in the methodologies exposed and possible further applications of these methodologies. The authors hope that reactions about their publication will ensue, and they would be grateful to reader(s) motivated by some of the research efforts exposed hereafter letting them know about these experiences.s
Part 1. Non-standard spatial statistics -- 1. Introduction: spatial statistics, - 2. Individual versus ecological analyses -- 3. Statistical models for spatial data: some linkages and communalities -- 4. Frequency distributions for simulated spatially autorcorrelated random variable -- 5. Understanding correlations among spatial random variables -- 6. Spatially structured random effects: a comparison of three popular specifications -- 7. Spatial filter versus conventional spatial model specifications: some comparisons -- 8. The role of spatial of autocorrelation in prioritizing sites within a geographic landscape -- 9. General spatial statistics conclusions -- 10. References: spatial statistics (Part 1) Part 2. Non-standard spatial econometrics -- 11. Introduction: spatial econometrics -- 12. Mixed linear-logarithmetic specification for Lotka-Volterra models with endogenously generated SDLS-variables -- 13. Selecting spatial regimes by threshold analysis -- 14. Finite automata -- 15 Learning from residuals -- 16. Verhulst and Poisson distributions -- 17. QUARLIREG: qualitative regression and its application to spatial data -- 18. Filtering complexity for observational errors and spatial bias -- 19. General spatial econometrics conclusions -- 20. References: spatial econometrics (Part 2).
Keywords: Geography; Economics; Migration; Geography; Geography (general).; Migration; Economics/Management Science, general